2009
DOI: 10.1029/2008wr007121
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface flow velocities in a hillslope with lateral preferential flow

Abstract: [1] Our understanding of hillslope subsurface flow relies on assumptions about how storm characteristics affect the hillslope runoff response. Experiments in hillslopes dominated by preferential flow features often show that runoff is dynamic and is affected by antecedent conditions, rainfall conditions, and position of the slope. We applied tracers to a hillslope under natural and steady state flow boundary conditions to determine the relationship between lateral tracer velocities and various hillslope length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 57 publications
8
74
0
Order By: Relevance
“…Steady-state flow was achieved by diverting water at a rate of 23.5 l min −1 from a nearby stream into a trench 30 m above the road cut-bank. The flow rate of 23.5 l min −1 was used because it produced similar lateral solute flow rates during tracer experiments conducted under steady-state and natural storm conditions (Anderson et al, 2009). Flow conditions were measured with tipping buckets installed at the road cut-bank and once steady-state flow was achieved, a concentrated solution of Brilliant Blue dye was added to the input trench to create a dye concentration of 4-5 g/l.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Steady-state flow was achieved by diverting water at a rate of 23.5 l min −1 from a nearby stream into a trench 30 m above the road cut-bank. The flow rate of 23.5 l min −1 was used because it produced similar lateral solute flow rates during tracer experiments conducted under steady-state and natural storm conditions (Anderson et al, 2009). Flow conditions were measured with tipping buckets installed at the road cut-bank and once steady-state flow was achieved, a concentrated solution of Brilliant Blue dye was added to the input trench to create a dye concentration of 4-5 g/l.…”
Section: Experimental Designmentioning
confidence: 99%
“…This experiment showed the presence of highly developed preferential flow paths corresponding to the largest contributing areas (greater than 1100 m 2 ). These areas also had the largest percentage of hillslope outflow during rainfall events and for steady state experiments (Anderson et al, 2009). Small contributing areas (less than 400 m 2 ) and relatively flat local topography (less than 15%) coincided with areas that had few preferential flow pathways.…”
Section: Modification Of Preferential Flow Pathsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that the measured outflow integrates the heterogeneous hydrological response of the soil in the hillslope, which can be governed by flow through the spatially and temporally variable soil macropores (Beven and Germann, 2013;Chappel, 2010). The primary role of the macropores in determining timing, peak and volume of the generated subsurface flow has been demonstrated in different large-scale investigations, that were primarily carried out in humid or temperate climates (Anderson et al, 2009;Dusek et al, 2012;Jost et al, 2012;Uchida et al, 2004). For example, Anderson et al (2009) found that the hydraulic connectivity of the preferential flow network at the hillslope scale was an important factor governing subsurface flow, and they were able to determine relationships between lateral flow, hillslope length and various storm indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, connection with a deep and regional aquifer we did not take into account in our modelling, could also affect the water table dynamics. The spatial variations of K c as well lateral preferential flow pathways in the weathered layers could significantly influence the spatial variations of the water table dynamics, as shown by Tromp-van Meerveld and Weiler (2008) in a heterogeneous soil/bedrock interface and by Anderson et al (2009b) in the soil macropores, using similarly Hill-vi model.…”
Section: Effect Of Spatial Variability Of Physical Properties On Discmentioning
confidence: 99%